Silver/Selenium/Chitosan-doped Hydroxyapatite coatings on biological NiTi alloy: In vitro biodegradation analysis - Say, Y.; Aksakal, B. (SPRINGER, 2019)
Nitinol (NiTi) substrates were bioceramic coated by single layer Hydroxyapatite (HA), double layer HA/Silver (Ag) and double-layered HA/Selenium (Se)-Chitosan (Cht) substitutions by sol-gel method. Surface morphologies and adhesion strengths of the obtained coatings were characterized by means of SEM, EDX, XRD, and adhesion tests. Crack-free coatings were obtained in single layer-HA (S-1), double layer HA/Ag (S-2), and double-layered HA/Selenium-Cht (S-3) coatings on NiTi alloys executed via the sol-gel method. Degradation behavior was analyzed in via simulated body fluid (SBF) environment by means of weight loss (%) and ion release rates for 1-4 weeks of immersion periods. The degraded coating particles were measured and metallic ions were detected quantitatively by an inductively coupled plasma-mass spectrometer (ICP-MS). The results show that such coatings could minimize and/or prevent the degradation of metallic ions and weight loss (%) from the coated substrates. From the overall results, HA/Ag double layer biocomposite (S-2)-coated NiTi substrates revealed the highest adhesion strength and lowest weight loss and degradation. It was also shown in all groups that the Ni ion release from the NiTi substrates was prevented by the coatings. [GRAPHICS] .
Keywords: Hydroxyapatite; Sol-gel coating; NiTi; Biodegradation; VIVO BIOCOMPATIBILITY; OXIDATIVE STRESS; CORROSION; TOXICITY; SELENIUM; PARTICLES; COMPOSITE; TITANIUM; SCAFFOLD; NICKEL; Materials Science